Dexamethasone dose and length of hospital stay among hospitalized COVID-19 patients: a retrospective cross-sectional study in Malaysia - Othman, Nurul Syafiqah; Mohd Taufek, Nor Hidayah; Jamaluddin, Wirdatul Ainna; Zin, Che Suraya (International Journal Of Community Medicine And Public Health, 2023)
Background: Dexamethasone is a potent corticosteroid that has been widely used as COVID-19 treatment. However, optimal dose of dexamethasone in COVID-19 treatment and how its different doses affect the patient outcomes is uncertain. This retrospective study aimed to evaluate the use of dexamethasone dose and length of hospital stay in COVID-19 patients admitted to two public hospitals in the east coast region of Malaysia between February 2020 and August 2021. Methods: This study included all hospitalized patients who were receiving dexamethasone during the study period. Dexamethasone doses were categorized into high dose (≥15 mg/day), moderate dose (7-14 mg/day) and low dose (≤6 mg/day). A multivariable logistic regression was conducted to evaluate the potential risk factors associated with length of hospital stays. Results: Of 119 patients enrolled, majority (40%) of patients received high dose dexamethasone, followed by 33% received moderate dose and 27% received low dose. Patients who received high doses were associated with extended hospital stays of 4-5 days and more frequently required mechanical ventilation. Multivariable logistic regression showed that elderly (OR=1.03; 95% CI=1.00-1.06, p=0.001) and severe stage of COVID-19 (stage 4-stage 5) upon hospital admission (OR=2.79; 95% CI=1.17-6.68, p=0.021) increased the risk of prolonged hospital stay. Conclusions: COVID-19 patients treated with high and moderate doses of dexamethasone were associated with longer hospital stay and required mechanical ventilation compared to those on low doses. Future studies are needed to provide more evidence on benefits of low dexamethasone dose in COVID-19 patients.